Multi-aromatic-ring polyarylene sulfide-metallate composite material, preparation method and application thereof, and flexible material
A polyaromatic ring polyarylene sulfide-metal acid salt composite material is developed to address bonding issues in flexible radiation shielding, offering high radiation resistance and shielding efficiency, suitable for space and extreme environments.
Patent Information
- Application Number
- CN202411295934.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-13
AI Technical Summary
Existing flexible radiation shielding materials lack stable interface bonding between polymer matrices and metal elements, leading to material instability and inadequate radiation shielding performance, especially under extreme conditions like lunar or space environments, and they are difficult to process into flexible, lightweight, and strong forms.
A polyaromatic ring polyarylene sulfide-metal acid salt composite material is prepared by copolymerizing a composite salt, aromatic polycyclic active units, and dihalogenated aromatic compounds under controlled conditions to enhance bonding and stability, which can then be spun into fibers or cast into films for radiation protection.
The composite material exhibits high temperature resistance, corrosion resistance, and effective radiation shielding, with gamma ray tolerance up to 10^8 Gy and X-ray shielding efficiency of ≥90% at ≤2.5 cm thickness, suitable for flexible radiation protection equipment.
Smart Images

Figure SMS_10 
Figure SMS_11 
Figure SMS_12
Abstract
Description
Technical Field
[0001] The invention specifically relates to a polyaromatic ring polyarylene sulfide-metal acid salt composite material, a preparation method, application and flexible material thereof, and belongs to the field of functional composite materials. Background Art
[0002] Accelerating space exploration and utilization is an important direction for the development of science and technology in this century. However, unlike the earth's environment, outer space lacks the protection of the atmosphere. The radiation generated by a large amount of high-energy rays and high-energy particle flows in the sun and the Milky Way can cause harm to personnel engaged in space exploration and affect the function and operation of equipment. The radiation level on the moon's surface is 2 to 3 times that of the International Space Station. Compared with the earth's surface, the radiation level on the moon's surface is already very high. When astronauts jump on the moon's surface, they will absorb about 60 microsieverts of radiation per hour, which is about 200 times the radiation dose on the earth's surface. The lack of magnetic field or atmospheric protection is the main reason for the high radiation force of the moon. The radiation on the moon comes from several different types of radiation sources, including high-energy cosmic rays and solar particle impacts. In addition, astronauts may also be threatened by neutrons and gamma rays produced by lunar soil and other forms of radiation.
[0003] The development of efficient radiation shielding and protection materials and equipment is key to the health and safety of practitioners. It is also one of the core factors in maintaining the safe and stable operation of electronic equipment and instruments, and the long-term and reliable storage of various information and data. It plays an important role in the country's space exploration, nuclear power and nuclear equipment, medical diagnosis and treatment and other fields.
[0004] As for the characteristics of radiation itself, in most cases, multiple radiations such as neutron radiation, alpha ions, gamma ray radiation, X-rays and other rays and their electromagnetic waves occur simultaneously and superimpose. Radiation of a single type of ray is not common, and each element has a certain weak absorption area for shielding and absorption of high-energy rays. The structure and performance of a single element material are difficult to meet the comprehensive shielding and protection of radiation.
[0005] Current status of flexible radiation shielding materials. Traditional composite materials are difficult to adapt to and meet the needs of space exploration, personal protection, equipment protection and other scenarios. Flexible radiation shielding materials can meet the needs of lightweight, wearable, plastic, foldable and other application scenarios, which is the current research hotspot and focus. At present, rubber radiation shielding materials are typical representatives of flexible radiation shielding materials. For example, lead-containing rubber protective clothing is currently widely used in nuclear power plants and radiation medical institutions. These materials are mainly formed by filling polymers with boron, lead and their compounds to form composite materials, which are processed into protective clothing of various shapes. This type of composite material is mainly prepared by mixing and blending processes, most of which belong to physical methods, with no chemical bond bonding at the interface and poor stability; in order to ensure flexibility, the content of lead boron and its compounds is low, and the shielding effect is limited. However, lead is highly toxic, and the energy range of 40 to 80 keV is called the "weak absorption zone" of lead. In this energy range, lead has a reflective effect on X-rays and its absorption capacity is very weak. Therefore, lead-free radiation shielding materials have become one of the research hotspots. For example, in 2016, MaghrabiHA et al. used lightweight and durable Bi2O3 coating to replace lead, and analyzed the shielding properties of textiles. The study found that bismuth oxide is effective in attenuating X-rays, and the X-ray shielding ability of polyester fabrics with more than 50% bismuth oxide is enhanced. At present, there is no mature technology in lead-free protective clothing in China, and its core functional materials are basically raw materials imported from abroad, such as the lead-free gamma-ray non-woven protective material of DEMRON in the United States. Moreover, the company's technologically backward products are about to be eliminated, and more advanced new products are subject to embargo restrictions on my country.
[0006] Common problems in the research of flexible radiation shielding materials. Although a large number of researchers have been engaged in the research of flexible radiation shielding and protective materials from theoretical and experimental aspects, and have published a large number of research papers and applied for a large number of patents, lightweight, efficient, and functionally integrated flexible radiation shielding and protective materials are still difficult to meet the large-scale application requirements in space exploration, employee protection, equipment and instrument protection, and other radiation scenarios.
[0007] According to the radiation protection materials currently used in radiation materials, they are mainly blended composite materials. Traditional plastics and rubbers are mainly blended with lead or other metal oxides or salts. For example, thermoplastics, such as PE (polyethylene), PS (polystyrene), and PMMA (polymethyl methacrylate), generally have a low operating temperature (not exceeding 150°C), and PTFE (polytetrafluoroethylene) with excellent heat resistance, corrosion resistance and self-lubricating properties has relatively poor radiation resistance; thermosetting plastics, such as epoxy resins and polyimides, cannot be deformed after curing and cannot be secondary molded; rubber (including natural rubber; silicone rubber, such as polydimethylsilane, PDMS; copolymerized synthetic rubber, such as styrene-ethylene-butadiene-styrene, SEBS) generally has no active groups, and it is difficult to form chemical bonds with various metal elements. There is no stable interface bonding, and there may be phase separation, resulting in material instability. In addition, it has good elasticity and low strength, and cannot meet the requirements in high stress environments. Therefore, how to combine the molecular level with the aggregation state, especially to improve the bonding ability between the polymer matrix and the metal elements and to improve the long-term stability of the composite material, is also one of the core issues that need to be solved in the research of new flexible radiation absorption and shielding materials.
[0008] Under extreme physical conditions such as lunar conditions, outer space conditions, and nuclear radiation conditions, in addition to radiation absorption and shielding performance, various properties of flexible materials such as heat and cold resistance, insulation performance, and corrosion resistance need to be optimized. In addition, lightweighting is also one of the core factors that need to be considered. Meeting the requirements of "flexible, tough, thin, light, wide, and strong" will greatly enhance the performance and function of flexible radiation shielding and protection materials, broaden their application scenarios, ensure the health and safety of practitioners, and ensure the safe operation of equipment and instruments.
[0009] Ideas and innovations of the present invention
[0010] The radiation resistance of general plastics is not good. Only a few special engineering plastics have different degrees of radiation resistance, such as POB, LCP, PVDF, PI, PPS, PEEK and PSF. PSF has excellent radiation resistance, LCP (Xydar) also has very good radiation resistance, and polyphenylene ester (POB) has excellent radiation resistance. 6 After irradiation with GY diamond rays, the mechanical properties remain unchanged. PI has good radiation resistance. 7 GY has little change in performance after radiation; PVDF has high radiation resistance and can withstand 3x10 7 Gy of irradiation; while PTFE is 8x10 5Under γ-ray radiation, it becomes brittle and cross-linked, and its radiation resistance is poor; PEEK has strong radiation resistance and high radiation resistance, which exceeds the best radiation resistance of polystyrene among general resins. γ-irradiation dose reaches 2*10 7 Gy can still maintain good insulation performance. Polyphenylene sulfide (PPS) has good radiation resistance, with a measurement of 1×10 8 Gy is unmatched by other engineering plastics and is widely used in electronics, military industry, and aerospace, and has become the largest special engineering plastic.
[0011] Among non-metallic elements, the mass attenuation coefficient of S is relatively large. At low and medium energies (0.1-10 MeV), the mass attenuation coefficient of H is relatively large. The neutron slowing efficiency of C and B elements is high. Rare earth elements such as gadolinium (Gd), tantalum (Ta), tungsten (W), samarium (Sm), europium (Eu) and bismuth (Bi) have large atomic numbers, and their gamma-ray and X-ray shielding effects, neutron absorption and interception coefficients are relatively good.
[0012] The previous research results of this team, announcement number CN110564154 B, disclosed a bonded polyarylene sulfide metal composite material with nuclear radiation protection function. However, our team found that when preparing bonded polyarylene sulfide metal composite materials: (1) These metals have low reactivity with active polyarylene sulfide. Some metals form chemical bonds, while others exist in a metallic state. They have excellent performance as radiation protection, but cannot meet the insulation performance requirements of flexible circuits and ionization protection layers of space equipment and may be punctured; (2) The active groups in the polymer molecular chains in CN110564154B are all smaller active dichloroaromatic compound molecules. The polymer molecular chains formed have good flexibility, which is manifested as a slightly higher melt index and good fluidity. Only when the slightly higher metal content reduces its fluidity can it be used for spinning or film drawing, resulting in lower electrical properties of the fibers and films, especially lower resistance, and increased dielectric loss; (3) Another problem with the bonded polyarylene sulfide metal composite materials of CN110564154B is that although the incompletely bonded metal can have excellent radiation absorption and protection performance, on the contrary, it can be detected and discovered by radiation, and further improvement is needed in terms of stealth protection of equipment and devices. Summary of the invention
[0013] The first technical problem solved by the present invention is to propose a method for preparing a polyaromatic ring polyarylene sulfide-metallate composite material. The polyaromatic ring polyarylene sulfide-metallate composite material prepared by the method can be used in different radiation shielding and protection scenarios, and the material of the present invention can be further obtained by melt spinning to obtain flexible fibers or by casting to obtain films, and then woven into various types of radiation protection cloths as flexible radiation protection equipment.
[0014] The preparation method of the polyaromatic ring polyarylene sulfide-metal acid salt composite material is as follows: under the protection of inert gas or N2, with polar aprotic solvent as the medium, the composite salt, aromatic polycyclic active unit, dihalogenated aromatic compound and sulfide are copolymerized under the action of catalyst and base to obtain the composite material;
[0015] Wherein, the composite salt is an insoluble metal acid salt, and the chemical formula is M a (N b O c ) d , where M is a rare earth element, N is W, Ta or Mo, O is an oxygen element, and a, b, c, d are all ≥ 1;
[0016] The aromatic polycyclic active unit is a dihalogenated polycyclic aromatic hydrocarbon containing an active group, or a dihalogenated polycyclic aromatic hydrocarbon that can be hydrolyzed under alkaline conditions to produce an active group, and the active group is at least one of -OH and -COOH;
[0017] The molar ratio of the aromatic polycyclic active monomer to the dihalogenated aromatic compound is 1-10:999-90.
[0018] The composite salt accounts for 0.5 to 20 wt% of the total weight of the composite material.
[0019] In one embodiment, the M a (N b O c ) d In the embodiment, M is Gd, Lu, Eu or Er, and N is W or Ta; preferably, M is Gd; more preferably, the M a (N b O c ) d In the middle, a:d=2:3; c:b=3~4:1;
[0020] In a specific embodiment, the composite salt is Gd2(WO4)3 or Gd2(Ta2O6)3.
[0021] In one embodiment, the aromatic polycyclic active unit is At least one of the following, wherein R1 and R2 are any one of halogens, and R1 and R2 are the same or different; preferably, the halogen is Cl or Br;
[0022] More preferably, the aromatic polycyclic active unit is:
[0023] At least one of .
[0024] In one embodiment, the dihalogenated aromatic compound is a para-dihalogenated or meta-dihalogenated aromatic compound; preferably, the dihalogenated aromatic compound is selected from: 1,4-dihalobenzene, 2,4-dihalobenzene, 3,5-dihalobenzene, 4,4'-dihalobenzene, 4,4'-dihalobiphenyl, 4,4'-dihalodiphenyl sulfone, 4,4'-dihalobenzophenone or 4,4'-dihalodiphenyl ether; more preferably, the dihalogenated aromatic compound is 1,4-dichlorobenzene, 2,4-meta-dichlorobenzene, 4,4'-dichlorodiphenyl sulfone or 4,4'-dichlorobenzophenone.
[0025] In one embodiment, the catalyst of the present invention is a lactone or a lactam; preferably, the lactone or lactam is γ-butyrolactone, γ-valerolactone, ε-caprolactone, δ-cyclopentanolactone; γ-butyrolactam, δ-valerolactam, ε-caprolactam and ω-enantholactam amine, etc.
[0026] Wherein, the amount of catalyst used is 5-20wt.% of sodium sulfide or sodium hydrosulfide.
[0027] In one embodiment, the sulfide is at least one of sodium sulfide, sodium hydrosulfide, potassium sulfide, potassium hydrosulfide, ammonium sulfide, and ammonium hydrosulfide; preferably, the sulfide is sodium sulfide or sodium hydrosulfide;
[0028] The amount of sulfide used is calculated as follows: the amount of sulfide: the sum of the amounts of aromatic polycyclic active units and dihalogenated aromatic compounds = 0.95-1.05:1.0.
[0029] In one embodiment, the polar aprotic solvent is selected from sulfone or sulfone compounds, amine compounds or lactam compounds; preferably, the polar aprotic solvent is selected from: at least one of N-methyl-2-pyrrolidone, N-ethylpyrrolidone, N-cyclohexylpyrrolidone, 1,3-dimethyl-2-imidazolone, hexamethylphosphoramide, N,N-dimethylacetamide, N,N-dimethylamide, caprolactam, N-ethylcaprolactam, N,N-vinylpyrrolidone, 1,3-dimethyl-2-imidazolidinone lactam, tetramethylurea, dimethyl sulfoxide or cyclopentane;
[0030] The amount of the polar aprotic solvent used is calculated according to the following ratio: the sum of the amounts of the aromatic polycyclic active units and the dihalogenated aromatic compounds: the volume of the polar aprotic solvent = 1: 250-1500 mL.
[0031] In one embodiment, the copolymerization reaction conditions are: reaction temperature is 200-300°C, reaction time is 1-12h; preferably, first react at 200-250°C for 2-6h, then react at 250-300°C for 3-6h; more preferably, react at 220°C for 3h, then react at 260°C for 3h.
[0032] In one embodiment, after the copolymerization reaction, the polyaromatic ring polyarylene sulfide-metal acid salt composite material is washed and dried; preferably, the washing method is, after the copolymerization reaction is completed, first cooling to ≤180°C, then adding water to mix, filtering, washing, and drying the polyaromatic ring polyarylene sulfide-metal acid salt composite material; more preferably, during washing, the temperature is reduced to below 150°C for washing.
[0033] The second technical problem solved by the present invention is to provide a polyaromatic ring polyarylene sulfide-metal acid salt composite material, which is prepared by any one of the above preparation methods.
[0034] The third technical problem solved by the present invention is to provide a polyaromatic ring polyarylene sulfide-metal acid salt composite flexible material. The composite flexible material is prepared by granulating, spinning and weaving the polyaromatic ring polyarylene sulfide-metal acid salt composite material;
[0035] Preferably, before spinning, the granulated copolymer composite material is dried; more preferably, a vacuum drum is used for drying; more preferably, the vacuum degree of the vacuum drum is 0.097 Pa, the drying temperature is 120-150° C., and the drying time is 12-16 hours;
[0036] Preferably, the spinning process is: the spinning temperature is 300-320°C, and the spinning speed is 600-1000m / min;
[0037] More preferably, the spun material is woven to obtain a polyaromatic ring polyarylene sulfide-metal acid salt composite flexible fabric.
[0038] The fourth technical problem solved by the present invention is to provide the use of the polyaromatic ring polyarylene sulfide-metal acid salt composite material and the polyaromatic ring polyarylene sulfide-metal acid salt composite flexible material. Both materials can be used for radiation shielding and protection.
[0039] Beneficial effects of the present invention:
[0040] The flexible polyarylene sulfide material prepared by the present invention can be arbitrarily cut and shaped after spinning and weaving, and can be used for radiation protection at different levels, in different scenes and in different fields. It has the functions of high temperature resistance, corrosion resistance, and radiation protection.
[0041] The material prepared by the present invention is easy to process and has good mechanical properties. Its melt index is 80-200g / 10min (test conditions are 315°C and load is 5kg); the fiber melting point is 280-290°C; the initial decomposition temperature is higher than 500°C; the fiber strength is greater than 4cN / dtex; it has good shielding properties against gamma rays, X-rays and other rays, and the gamma ray (the maximum radiation dose that can be tolerated when the material strength remains above 90%, that is, when it decreases by no more than 10%): 10 8Gy; when the shielding efficiency for X-ray (1meV) is ≥90%, its thickness is ≤2.5cm. DETAILED DESCRIPTION
[0042] The preparation method of the polyaromatic ring polyarylene sulfide-metal acid salt composite material is as follows: under the protection of inert gas or N2, with polar aprotic solvent as the medium, the composite salt, aromatic polycyclic active unit, dihalogenated aromatic compound and sulfide are copolymerized under the action of catalyst and base to obtain the composite material;
[0043] In the scheme of the present invention, the composite salt serves as an enhanced phase for high-energy particle and radiation shielding; the aromatic polycyclic active unit serves to enhance the rigidity and polarity of polyphenylene sulfide and improve the interface bonding and stability between polyphenylene sulfide and nano-gadolinium tungstate (tantalate) composite salt.
[0044] The composite salt is an insoluble metal acid salt, and its chemical formula is M a (N b O c ) d , where M is a rare earth element, N is W, Ta or Mo, O is an oxygen element, and a, b, c, d are all ≥ 1;
[0045] The aromatic polycyclic active unit is a dihalogenated polycyclic aromatic hydrocarbon containing an active group, or a dihalogenated polycyclic aromatic hydrocarbon that can be hydrolyzed under alkaline conditions to produce an active group, and the active group is at least one of -OH and -COOH;
[0046] The molar ratio of the aromatic polycyclic active monomer to the dihalogenated aromatic compound is 1 to 10:999 to 90. The ratio of the aromatic polycyclic active monomer to the dihalogenated aromatic compound needs to be limited within this range. If it is not within this ratio range, when the ratio of the aromatic polycyclic active unit is too high, the regularity of the polymer chain will be reduced, the polycyclic rotation will be difficult, and the flexibility of the polymer will be reduced; if the ratio is too low, there will be fewer active groups, the binding force with the anti-radiation composite salt will be weakened, and its interface stability will be reduced.
[0047] The composite salt accounts for 0.5-20wt% of the total weight of the composite material. If the amount of the composite salt added is too high, the material becomes too rigid, and it is difficult to be processed into fibers and films, and the goal of flexible application cannot be achieved.
[0048] Compared with CN110564154 B, the present invention adopts a composite salt. The prepared composite salt has no free electrons and is difficult to ionize, and has excellent insulation performance, thereby avoiding problems such as leakage and short circuit breakdown when used as a radiation protection flexible material. At the same time, the aromatic polycyclic active monomer is selected, and its polymer molecular chain has high rigidity and is difficult to rotate, which is manifested in its low melt index and easy processing into fibers and films, and is suitable for complex geometric scenes. In addition, since the polyaromatic ring polyarylene sulfide-metal acid salt composite material formed with the composite salt is a high insulation material, the means based on the identification and detection of free electrons cannot be used for the detection of the material, and it has a wider range of uses in stealth and confidentiality protection.
[0049] In one embodiment, the M a (N b O c ) d In the embodiment, M is Gd, Lu, Eu or Er, and N is W or Ta; preferably, M is Gd; more preferably, the M a (N b O c ) d In the middle, a:d=2:3; c:b=3~4:1;
[0050] In a specific embodiment, the composite salt is Gd2(WO4)3 or Gd2(Ta2O6)3.
[0051] The composite salt of the present invention has different preparation methods, and the present invention preferably adopts double decomposition reaction.
[0052] In a specific embodiment, the composite salt is prepared by double decomposition. Taking the preparation of gadolinium tungstate (tantalate) composite salt as an example, the reaction formula is:
[0053] 2Gd(NO3)3·6H2O+3Na2WO4→Gd2(WO4)3↓+6NaNO3
[0054] 2Gd(NO3)3·6H2O+3·Na2Ta2O6→Gd2(Ta2O6)3↓+6NaNO3
[0055] In this reaction, gadolinium nitrate or other soluble gadolinium salts can be used as gadolinium donors; soluble metal acid salts such as sodium tungstate, sodium tantalate, sodium molybdate, etc. are selected as donors of other metal elements such as tungsten, tantalum and molybdenum. Through stoichiometric proportions, the reaction is carried out in the solution to obtain a multi-metal insoluble composite salt with radiation shielding and protection effects. The molar ratio of soluble gadolinium salt to tungstate or tantalate is: 1:0.95-1.05 (mol). The composite salt monomers that can be selected are but not limited to the following: sodium tungstate, sodium tantalate, gadolinium nitrate, lutetium nitrate, europium nitrate, erbium nitrate, etc.
[0056] In one embodiment, the aromatic polycyclic active unit is At least one of the following, wherein R1 and R2 are any one of halogens, and R1 and R2 are the same or different; preferably, the halogen is Cl or Br;
[0057] More preferably, the aromatic polycyclic active unit is:
[0058] (2',7'-dichloro-3',6'-dihydroxyspiro[isobenzofuran-1(3H),9'-(9H)xanthen]-3-one, hereinafter referred to as Ia),
[0059] (1,7-dibromo-3,4,9,10-perylenetetracarboxylic dianhydride, hereinafter referred to as IIa), (2-(2,7-dichloro-3,6-dihydroxy-9H-xanthen-9-yl)benzoic acid, hereinafter referred to as IIIa) and (3′,6′-dichlorofluorescent orange-red, hereinafter referred to as IVa for this compound) at least one of the following.
[0060] In one embodiment, the dihalogenated aromatic compound is a para-dihalogenated or meta-dihalogenated aromatic compound; preferably, the dihalogenated aromatic compound is selected from: 1,4-dihalobenzene, 2,4-dihalobenzene, 3,5-dihalobenzene, 4,4'-dihalobenzene, 4,4'-dihalobiphenyl, 4,4'-dihalodiphenyl sulfone, 4,4'-dihalobenzophenone or 4,4'-dihalodiphenyl ether; more preferably, the dihalogenated aromatic compound is 1,4-dichlorobenzene, 2,4-meta-dichlorobenzene, 4,4'-dichlorodiphenyl sulfone or 4,4'-dichlorobenzophenone.
[0061] In one embodiment, the catalyst of the present invention is a lactone or a lactam; preferably, the lactone or lactam is γ-butyrolactone, γ-valerolactone, ε-caprolactone, δ-cyclopentanolactone; γ-butyrolactam, δ-valerolactam, ε-caprolactam and ω-enantholactam amine, etc.
[0062] Wherein, the amount of catalyst used is 5-20wt.% of sodium sulfide or sodium hydrosulfide.
[0063] In one embodiment, the sulfide is at least one of sodium sulfide, sodium hydrosulfide, potassium sulfide, potassium hydrosulfide, ammonium sulfide, and ammonium hydrosulfide; preferably, the sulfide is sodium sulfide or sodium hydrosulfide;
[0064] The amount of sulfide used is calculated as follows: the amount of sulfide: the sum of the amounts of aromatic polycyclic active units and dihalogenated aromatic compounds = 0.95-1.05:1.0.
[0065] In one embodiment, the polar aprotic solvent is selected from sulfone or sulfone compounds, amine compounds or lactam compounds; preferably, the polar aprotic solvent is selected from: at least one of N-methyl-2-pyrrolidone, N-ethylpyrrolidone, N-cyclohexylpyrrolidone, 1,3-dimethyl-2-imidazolone, hexamethylphosphoramide, N,N-dimethylacetamide, N,N-dimethylamide, caprolactam, N-ethylcaprolactam, N,N-vinylpyrrolidone, 1,3-dimethyl-2-imidazolidinone lactam, tetramethylurea, dimethyl sulfoxide or cyclopentane;
[0066] The amount of the polar aprotic solvent used is calculated according to the following ratio: the sum of the amounts of the aromatic polycyclic active units and the dihalogenated aromatic compounds: the volume of the polar aprotic solvent = 1: 250-1500 mL.
[0067] In one embodiment, the copolymerization reaction conditions are: reaction temperature is 200-300°C, reaction time is 1-12h; preferably, first react at 200-250°C for 2-6h, then react at 250-300°C for 3-6h; more preferably, react at 220°C for 3h, then react at 260°C for 3h.
[0068] In a specific embodiment, the copolymerization is carried out under pressure under the protection of an inert gas or nitrogen. After washing the composite salt water to remove the soluble metal ions, the slurry is added to a polar aprotic solvent according to the stoichiometry, and the water in the composite salt is removed by stirring and heating under the protection of nitrogen to obtain a composite salt suspension. The sulfide is stirred and heated under the protection of nitrogen or an inert gas to remove the water in the sulfide, and then cooled, the composite salt suspension is added, and the monomers (Ia)-(IVa) and the dihalobenzene reaction monomer are added. After replacing the air with nitrogen or an inert gas, the temperature is raised and the polymerization is performed under pressure. The polymerization is carried out at 200-250°C for 2-6 hours, then at 250-300°C for 3-6 hours, and then the temperature is lowered to below 150°C to complete the polymerization.
[0069] In the present invention, it is necessary to remove the water in the reactants before the polymerization reaction. If the reactants contain a large amount of water, the presence of water will cause the sulfide ions to react with the metal ions and affect the polymerization.
[0070] In a specific embodiment, in order to remove water from the composite salt, the composite salt is preferably first prepared into a paste, then prepared into a metal salt suspension, and then heated to remove the water therein.
[0071] In a specific embodiment, the sulfide can be selected as 45% or 60% low-iron sodium sulfide or 35-45% low-iron sodium hydrosulfide as the initial raw material, and then the water in the solution is removed by heating, and finally the dried sulfide is used for polymerization.
[0072] Since the sulfide in the sulfide aqueous solution is easily hydrolyzed, it is necessary to add some sodium hydroxide to the aqueous solution to prevent the sulfide from hydrolyzing.
[0073] The specific operation of removing water from the sulfide aqueous solution of the present invention is: mixing the polar aprotic solvent, the sulfide aqueous solution and sodium hydroxide, stirring, heating to 190-200° C. under nitrogen protection, and fractionating water.
[0074] In one embodiment, after the sulfide is fractionated to remove water, it is cooled to 130°C (it can also be cooled to room temperature, but it takes longer and the subsequent polymerization also requires a longer temperature rise, which is not an efficient option), and then mixed with the composite salt suspension, aromatic polycyclic active units, and dihalogenated aromatic compounds, and polymerized in a pressure vessel.
[0075] In one embodiment, the composite material needs to be washed and dried. The specific method can be: transfer the composite material into deionized water, stir, filter to remove soluble ions such as soluble sodium chloride, wash with deionized water for 6 to 9 times, and then dry.
[0076] Preferably, the washing method is, after the copolymerization reaction is completed, first cooling to ≤180°C, adding deionized water while stirring, filtering, washing and drying; more preferably, during washing, the temperature is lowered to below 150°C for washing.
[0077] In one embodiment, the reaction process of the present invention is as follows:
[0078] Take active monomer Ia and Gd2(WO4)3 as an example:
[0079]
[0080] Take active monomer IIa and Gd2(WO4)3 as an example:
[0081]
[0082] Take active monomer IIIa and Gd2(WO4)3 as an example:
[0083]
[0084] The second technical problem solved by the present invention is to provide a polyaromatic ring polyarylene sulfide-metal acid salt composite material, which is prepared by any one of the above preparation methods.
[0085] The typical composition and structure of the polyaromatic ring polyarylene sulfide-metal acid salt composite material of the present invention are shown as follows:
[0086] (1): 3',6'-dihydroxyspiro[isobenzofuran-1(3H),9'-(9H)xanthen]-3-one structure
[0087]
[0088] (2) Structure of 1,7-dibromo-3,4,9,10-perylenetetracarboxylic dianhydride
[0089]
[0090] (3) Structure of 2-(-3,6-dihydroxy-9H-xanthene-9-yl)benzoic acid
[0091]
[0092] (4) 3,6-fluorescent orange-red structure
[0093]
[0094] The third technical problem solved by the present invention is to provide a polyaromatic ring polyarylene sulfide-metal acid salt composite flexible material. The composite flexible material is prepared by granulating, spinning and weaving the polyaromatic ring polyarylene sulfide-metal acid salt composite material;
[0095] Preferably, the granulation method is: the copolymer complex is extruded and granulated by a twin-screw extruder;
[0096] Preferably, before spinning, the granulated copolymer composite material is dried; more preferably, a vacuum drum is used for drying; more preferably, the vacuum degree of the vacuum drum is 0.097 Pa, the drying temperature is 120-150° C., and the drying time is 12-16 hours;
[0097] Preferably, the spinning process is: the spinning temperature is 300-320°C, and the spinning speed is 600-1000m / min;
[0098] More preferably, the spun material is woven to obtain a polyaromatic ring polyarylene sulfide-metal acid salt composite flexible fabric.
[0099] The fourth technical problem solved by the present invention is to provide the use of the polyaromatic ring polyarylene sulfide-metal acid salt composite material and the polyaromatic ring polyarylene sulfide-metal acid salt composite flexible material. Both materials can be used for radiation shielding and protection.
[0100] The above contents of the present invention are further described in detail below through the specific implementation methods of the embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. Various substitutions or changes made according to common technical knowledge and customary means in the art without departing from the above technical concept of the present invention should be included in the scope of the present invention.
[0101] The test tools and methods of the embodiments and comparative examples of the present invention are as follows:
[0102] i: Melt index meter: melt index of copolymer composite;
[0103] ii: Thermal performance comparison: DSC, TGA analysis
[0104] iii: Fiber tensile strength: Use YG001N electronic single fiber strength tester;
[0105] iv: Gamma ray absorption shielding test: irradiation with energy of 10 5 Gy starts at 10 15 Gy, 10 18 Gy is the highest dose.
[0106] v: X-ray test: GB 16363-1996, Shielding performance and test methods of X-ray protective materials, ≤400kv.
[0107] The tests of the present invention are all completed by third-party testing.
[0108] Example 1 (Gadolinium Tungstate-Ia)
[0109] (1) Preparation of metal salt paste
[0110] 1.76 kg of sodium tungstate was added to 10 L of deionized water, and stirred at room temperature until completely dissolved to obtain a sodium tungstate solution; 1.81 kg of gadolinium nitrate hexahydrate crystals were added to 10 L of ethanol, and stirred for half an hour until completely dissolved, and then added to the sodium tungstate solution; stirred and gradually heated to 60° C., and continued stirring for 3 hours, and allowed to stand overnight, and filtered to obtain a white condensed milk-like gadolinium tungstate paste, and the water content was 55±2.5% according to the water content measurement.
[0111] (2) Preparation of metal salt-NMP suspension
[0112] Weigh 0.67 kg of the gadolinium tungstate paste obtained in step (1) in a beaker, add 2 L of NMP solvent, disperse evenly by ultrasonication, transfer to a 10 L atmospheric pressure reactor with stirring, wash the beaker twice with NMP, add the washing liquid into the reactor, and use a total of 12 L of NMP. Stir under nitrogen protection, gradually raise the temperature to 200 ° C, fractionate water (containing a small amount of NMP), and then cool to 120 ° C to obtain a -NMP suspension for use.
[0113] (3) Preparation of polyaromatic polyarylene sulfide-metal salt composites
[0114] 12 L of NMP, 5.2 kg of low-iron sodium sulfide (Na2S content of 45%) and 30 g of sodium hydroxide were added to a 30 L autoclave, stirred, heated to 200 ° C under nitrogen protection, 3.10 L of water (containing a small amount of NMP) was fractionated, and then cooled to 130 ° C, and then the gadolinium tungstate-NMP suspension obtained in step (2) was added to the reactor, 301 g of Ia, 4.30 kg of p-dichlorobenzene and 0.25 kg of γ-butyrolactone were added, and reacted at 220 ° C for 3 hours under nitrogen protection to form a uniform low molecular weight polymer; the temperature was raised to 260 ° C for reaction for 3 hours, cooled to 120 ° C, deionized water was slowly added, filtered, washed 6 times, each time soaked in 80 ° C deionized water for 20 minutes and filtered, and then dried at 110 ° C for 24 hours to obtain 3.35 kg of orange fine particles.
[0115] (4) Granulation
[0116] The orange particles obtained in step (3) were extruded and granulated at 320° C. using a twin-screw extruder to obtain copolymer composite pellets.
[0117] (5) Spinning
[0118] The composite pellets obtained in step (4) were dried by vacuum drum, the vacuum degree was 0.097 Pa, the drying temperature was 135°C, and the drying time was 15 hours. The preparation process of the nascent fiber: the spinning temperature was 320°C, and the spinning speed was 600m / min. The nascent fiber was heat stretched and heat set on a drawing machine, the stretching temperature was 120°C, and the setting temperature was 180°C. The final fiber diameter was 0.5±0.05mm.
[0119] (6) Weaving
[0120] The fiber obtained in step (5) is woven into a cloth with a thickness of 0.5 mm by a micro automatic loom, a width of 30 cm, a weft density range of 100 strands / inch, and a machine speed of 30 weft insertions per minute.
[0121] (7) Testing
[0122] The obtained copolymer fabric with a width of 30 cm was subjected to single-layer and multi-layer radiation protection performance tests, including the following tests: i. Testing the melt index of the copolymer composite; ii. Testing the melting point and decomposition temperature of the copolymer composite; iii. Testing the fiber strength (cN / dtex); iv. Testing the radiation resistance; γ-ray absorption shielding test: irradiation with an energy of 10 5 Gy starts at 10 15 , 10 18 Gy is the highest measurement; v. The thickness of the flexible material (cm) when the X-ray (1meV) shielding efficiency is ≥90%.
[0123] Test results:
[0124] i: Melt index (g / 10min, 315°C, 5kg): 105;
[0125] ii: Fiber melting point (℃): 283; Initial decomposition temperature (℃): 516;
[0126] iii: Fiber strength (cN / dtex): 4.5;
[0127] iv: gamma ray resistance (irradiation intensity does not drop by more than 10% of the dose): 10 8 Gy;
[0128] v: X-ray (1meV) shielding efficiency (%) ≥90: 2.5cm.
[0129] Example 2 (Gadolinium Tantalate-Ia)
[0130] This embodiment 2 is based on embodiment 1, and only step (1) is changed.
[0131] (1): Based on step (1) of Example 1, only "adding 1.76 kg of sodium tungstate to 10 L of deionized water" was changed to "adding 1.51 kg of sodium tantalate to 10 L of deionized water", and the rest of the process remained unchanged, to obtain a white condensed milk-like gadolinium tantalate paste, the water content of which was 55±2.5% as measured by moisture content measurement.
[0132] (2) Then, 0.67 kg of gadolinium tantalate paste was taken and the steps (2-7) of Example 1 were followed, except that gadolinium tungstate was replaced with gadolinium tantalate, and the rest of the process remained unchanged to obtain a fabric with a thickness of 0.5 mm.
[0133] Test results:
[0134] i: Melt index (g / 10min, 315°C, 5kg): 101;
[0135] ii: Fiber melting point (℃): 285; Initial decomposition temperature (℃): 513;
[0136] iii: Fiber strength (cN / dtex): 4.5;
[0137] iv: gamma ray resistance (irradiation intensity does not drop by more than 10% of the dose): 10 8 Gy;
[0138] v: X-ray (1meV) shielding efficiency (%) ≥90: 2.5 (cm).
[0139] Example 3 (gadolinium tungstate-IIa).
[0140] This embodiment 3 is based on embodiment 1, and only step (3) is changed.
[0141] (1) Prepare gadolinium tungstate paste according to step (1) of Example 1;
[0142] (2) Then, 0.67 kg of gadolinium tungstate paste was taken and a gadolinium tungstate-NMP suspension was prepared according to step (2) of Example 1.
[0143] (3) Based on step (3) of Example 1, only "add 301 g of Ia" was changed to "add 413 g of IIa", and the rest of the process remained unchanged, to obtain 3.36 kg of orange fine particles.
[0144] (4) The orange fine granules were then granulated, spun and woven according to steps (4-7) of Example 1 to obtain a cloth with a thickness of 0.5 mm.
[0145] Test results:
[0146] i: Melt index (g / 10min, 315°C, 5kg): 95;
[0147] ii: Fiber melting point (℃): 287; Initial decomposition temperature (℃): 517;
[0148] iii: Fiber strength (cN / dtex): 4.6;
[0149] iv: gamma ray resistance (irradiation intensity does not drop by more than 10% of the dose): 10 8 Gy;
[0150] v: X-ray (1meV) shielding efficiency (%) ≥90: 2.5 (cm).
[0151] Example 4 (Gadolinium Tungstate-IIIa)
[0152] This embodiment 4 is based on embodiment 1, and only step (3) is changed.
[0153] (1) Prepare gadolinium tungstate paste according to step (1) of Example 1;
[0154] (2) Then, 0.67 kg of gadolinium tungstate paste was taken and a gadolinium tungstate-NMP suspension was prepared according to step (2) of Example 1.
[0155] (3) Based on step (3) of Example 1, only "add 301 g of Ia" was changed to "add 309 g of IIIa", and the rest of the process remained unchanged, to obtain 3.33 kg of orange fine particles.
[0156] (4) The orange fine granules were then granulated, spun and woven according to steps (4-7) of Example 1 to obtain a cloth with a thickness of 0.5 mm.
[0157] Test results:
[0158] i: Melt index (g / 10min, 315°C, 5kg): 102;
[0159] ii: Fiber melting point (℃): 283; Initial decomposition temperature (℃): 511;
[0160] iii: Fiber strength (cN / dtex): 4.6;
[0161] iv: gamma ray resistance (irradiation intensity does not drop by more than 10% of the dose): 10 8 Gy;
[0162] v: X-ray (1meV) shielding efficiency (%) ≥90: 2.5 (cm).
[0163] Example 5 (Gadolinium Tungstate-IVa)
[0164] This embodiment 5 is based on embodiment 1, and only step (3) is changed.
[0165] (1) Prepare gadolinium tungstate paste according to step (1) of Example 1;
[0166] (2) Then, 0.67 kg of gadolinium tungstate paste was taken and a gadolinium tungstate-NMP suspension was prepared according to step (2) of Example 1.
[0167] (3) Based on step (3) of Example 1, only "add 301 g Ia" was changed to "add 283 g IVa", and the rest of the process remained unchanged, to obtain 3.32 kg of orange fine particles.
[0168] (4) The orange fine granules were then granulated, spun and woven according to steps (4-7) of Example 1 to obtain a cloth with a thickness of 0.5 mm.
[0169] Test results:
[0170] i: Melt index (g / 10min, 315℃, 5kg): 97;
[0171] ii: Fiber melting point (℃): 286; Initial decomposition temperature (℃): 516;
[0172] iii: Fiber strength (cN / dtex): 4.5;
[0173] iv: gamma ray resistance (irradiation intensity does not drop by more than 10% of the dose): 10 8 Gy;
[0174] v: X-ray (1meV) shielding efficiency (%) ≥90: 2.5cm.
[0175] Example 6 (Gadolinium Tungstate-Ia, Varying Ia Content)
[0176] (1) Prepare gadolinium tungstate paste according to step (1) of Example 1;
[0177] (2) Then, 0.67 kg of gadolinium tungstate paste was taken and a gadolinium tungstate-NMP suspension was prepared according to step (2) of Example 1.
[0178] (3) Based on step (3) of Example 1, "301 g Ia" was changed to "601 g Ia", "4.30 kg p-dichlorobenzene" was changed to "4.14 kg p-dichlorobenzene", and "0.25 kg γ-butyrolactone" was changed to "0.25 kg δ-valerolactam". The rest of the process remained unchanged, and 3.36 kg of orange fine particles were obtained.
[0179] (4) The orange fine granules were then granulated, spun and woven according to steps (4-7) of Example 1 to obtain a cloth with a thickness of 0.5 mm.
[0180] Test results:
[0181] i: Melt index (g / 10min, 315°C, 5kg): 188;
[0182] ii: Fiber melting point (℃): 285; Initial decomposition temperature (℃): 515;
[0183] iii: Fiber strength (cN / dtex): 4.5;
[0184] iv: gamma ray resistance (irradiation intensity does not drop by more than 10% of the dose): 10 8 Gy;
[0185] v: X-ray (1meV) shielding efficiency (%) ≥90: 2.5 (cm).
[0186] Example 7 (Gadolinium tungstate-Ia, only the content of gadolinium tungstate is different)
[0187] (1) Prepare gadolinium tungstate paste according to step (1) of Example 1;
[0188] (2) Based on step (2) of Example 1, only "weigh 0.67 kg of the gadolinium tungstate paste obtained in step (1) in a beaker" is changed to "weigh 0.38 kg of the gadolinium tungstate paste obtained in step (1) in a beaker", and the rest of the process remains unchanged to obtain a gadolinium tungstate-NMP suspension.
[0189] (3) Then, according to the process of step (3-7) of Example 1, a cloth with a thickness of 0.5 mm is obtained.
[0190] Test results:
[0191] i: Melt index (g / 10min, 315°C, 5kg): 185;
[0192] ii: Fiber melting point (℃): 282; Initial decomposition temperature (℃): 512;
[0193] iii: Fiber strength (cN / dtex): 4.6;
[0194] iv: gamma ray resistance (irradiation intensity does not drop by more than 10% of the dose): 10 8 Gy;
[0195] v: X-ray (1meV) shielding efficiency (%) ≥90: 2.5 (cm).
[0196] Example 8 (gadolinium tungstate-IIa, different IIa contents)
[0197] (1) Prepare gadolinium tungstate paste according to step (1) of Example 1;
[0198] (2) Then, 0.67 kg of gadolinium tungstate paste was taken and a gadolinium tungstate-NMP suspension was prepared according to step (2) of Example 1.
[0199] (3) Based on step (3) of Example 1, "301 g Ia, 4.30 kg p-dichlorobenzene" was changed to "765 g IIa, 4.15 kg p-dichlorobenzene", and the rest of the process remained unchanged to obtain 3.36 kg of orange fine particles.
[0200] (4) Then, according to the process of step (4-7) of Example 1, a cloth with a thickness of 0.5 mm is obtained.
[0201] Test results:
[0202] i: Melt index (g / 10min, 315℃, 5kg): 135;
[0203] ii: Fiber melting point (℃): 282; Initial decomposition temperature (℃): 515;
[0204] iii: Fiber strength (cN / dtex): 4.4;
[0205] iv: gamma ray resistance (irradiation intensity does not drop by more than 10% of the dose): 10 8 Gy;
[0206] v: X-ray (1meV) shielding efficiency (%) ≥90: 2.5 (cm).
[0207] Example 9 (gadolinium tantalate-Ia, with different gadolinium tantalate content from Example 2)
[0208] (1) According to the process of step (1) of Example 2, a white condensed milk-like gadolinium tantalate paste is obtained;
[0209] (2) Based on step (2) of Example 1, the step “weighing 0.67 kg of the gadolinium tungstate paste obtained in (1) into a beaker” was changed to “weighing 0.39 kg of the gadolinium tantalate paste obtained in (1) into a beaker”, and the rest of the process remained unchanged to obtain a gadolinium tantalate-NMP suspension.
[0210] (3) Then, according to the process of step (3-7) of Example 1, a cloth with a thickness of 0.5 mm is obtained.
[0211] Test results:
[0212] i: Melt index (g / 10min, 315°C, 5kg): 190;
[0213] ii: Fiber melting point (℃): 285; Initial decomposition temperature (℃): 515;
[0214] iii: Fiber strength (cN / dtex): 4.6;
[0215] iv: gamma ray resistance (irradiation intensity does not drop by more than 10% of the dose): 10 8 Gy;
[0216] v: X-ray (1meV) shielding efficiency (%) ≥90: 2.5 (cm).
[0217] Example 10 (gadolinium tungstate-IIa, IIa content is different from that of Example 3)
[0218] (1) According to the process of step (1) of Example 1, a white condensed milk-like gadolinium tungstate paste was obtained.
[0219] (2) Based on step (2) of Example 1, the step “weighing 0.67 kg of the gadolinium tungstate paste obtained in (1) into a beaker” was changed to “weighing 0.36 kg of the gadolinium tungstate obtained in (1) into a beaker”, and the rest of the process remained unchanged to obtain a gadolinium tungstate-NMP suspension.
[0220] (3) Based on step (3) of Example 1, “add 301 g of Ia and 4.30 kg of p-dichlorobenzene” was changed to “add 825 g of IIa and 4.14 kg of p-dichlorobenzene”, and the rest of the process remained unchanged to obtain 3.36 kg of orange fine particles.
[0221] (4) Then, according to the process of step (4-7) of Example 1, a cloth with a thickness of 0.5 mm is obtained.
[0222] Test results:
[0223] i: Melt index (g / 10min, 315°C, 5kg): 180;
[0224] ii: Fiber melting point (℃): 283; Initial decomposition temperature (℃): 513;
[0225] iii: Fiber strength (cN / dtex): 4.5;
[0226] iv: gamma ray resistance (irradiation intensity does not drop by more than 10% of the dose): 10 8 Gy;
[0227] v: X-ray (1meV) shielding efficiency (%) ≥90: 2.5cm.
[0228] Comparative Example 1 (no polycyclic active monomer or composite salt involved in polymerization)
[0229] Add 2.5L NMP, 200g NaOH, 1258g low-iron sodium hydrosulfide solution (Na2S content is 45%) into a 10L reactor, stir under nitrogen protection, heat to 200°C, distill out 790ml of water, add 735g of p-dichlorobenzene, react at 220°C for 3 hours, and the first stage of the reaction is completed; heat to 260°C and react for 3 hours, cool to 150°C, slowly add deionized water, filter, wash, and dry at 110°C for 24 hours to obtain 500g of a white product.
[0230] The white product was then granulated, spun and woven according to steps (4-7) of Example 1 to obtain a cloth with a thickness of 0.5 mm.
[0231] Test results:
[0232] i: Melt index (g / 10min, 315℃, 5kg): 380;
[0233] ii: Fiber melting point (℃): 281; Initial decomposition temperature (℃): 496
[0234] iii: Fiber strength (cN / dtex): 3.2 (20% lower than the example)
[0235] iv: gamma ray resistance (irradiation intensity does not drop by more than 10% of the dose): 10 8 Gy
[0236] v: X-ray (1meV) shielding efficiency (%) only ≥50: 2.5 (cm) (shielding rate cannot reach 90%)
[0237] Comparative Example 2 (adding only polycyclic active monomer)
[0238] In a 30L autoclave, 12L of NMP, 5.2kg of low-iron sodium sulfide (Na2S content 45wt%) and 30g of sodium hydroxide were added, stirred, heated to 200°C under nitrogen protection, 3.10L of water (containing a small amount of NMP) was fractionated, then cooled to 130°C, 301g of Ia, 4.30kg of p-dichlorobenzene, and 0.25kg of γ-butyrolactone were added, and reacted at 220°C for 3 hours under nitrogen protection to form a uniform low-molecular polymer; the temperature was raised to 260°C for reaction for 3 hours, cooled to 120°C, deionized water was slowly added, filtered, washed 6 times, each time soaked in 80°C deionized water for 20 minutes and filtered, and then dried at 110°C for 24 hours to obtain 3.03kg of an orange product.
[0239] The orange product was then granulated, spun and woven according to steps (4-7) of Example 1 to obtain a cloth with a thickness of 0.5 mm.
[0240] Test results:
[0241] i: Melt index (g / 10min, 315℃, 5kg): 360;
[0242] ii: Fiber melting point (℃): 280; Initial decomposition temperature (℃): 498
[0243] iii: Fiber strength (cN / dtex): 3.2 (20% lower than the example)
[0244] iv: gamma ray resistance (irradiation intensity does not drop by more than 10% of the dose Gy): 10 8
[0245] v: X-ray (1meV) shielding efficiency (%) only ≥50: 2.5 (cm) (shielding rate cannot reach 90%)
[0246] Comparative Example 3 (Polymerization with Gadolinium Tungstate but without Polycyclic Active Monomer)
[0247] This comparative example is modified on the basis of Example 1.
[0248] (1) Prepare gadolinium tungstate paste according to step (1) of Example 1;
[0249] (2) Then, 0.67 kg of gadolinium tungstate paste was taken and a gadolinium tungstate-NMP suspension was prepared according to step (2) of Example 1.
[0250] (3) Add 12 L of NMP, 5.2 kg of low-iron sodium sulfide (Na2S content 45 wt%) and 30 g of sodium hydroxide into a 30 L autoclave, stir, heat to 200 ° C under nitrogen protection, distill out 3.10 L of water (containing a small amount of NMP), then cool to 130 ° C, then add the gadolinium tungstate-NMP suspension obtained in step (2) into the reactor, add 4.41 kg of p-dichlorobenzene and 0.25 kg of γ-butyrolactone, react at 220 ° C for 3 hours under nitrogen protection to form a uniform low molecular weight polymer; heat to 260 ° C for 3 hours, cool to 120 ° C, slowly add deionized water, filter, wash 6 times, soak in 80 ° C deionized water for 20 minutes each time and filter, then dry at 110 ° C for 24 hours to obtain 3.35 kg of orange fine particles.
[0251] (4) The orange fine granules were then granulated, spun and woven according to steps (4-7) of Example 1 to obtain a cloth with a thickness of 0.5 mm.
[0252] Test results:
[0253] i: Melt index (g / 10min, 315℃, 5kg): 260;
[0254] ii: Fiber melting point (℃): 283; Initial decomposition temperature (℃): 500
[0255] iii: Fiber strength (cN / dtex): 3.2 (20% lower than the example)
[0256] iv: gamma ray resistance (irradiation intensity does not drop by more than 10% of the dose): 10 8 Gy
[0257] v: X-ray (1meV) shielding efficiency (%) ≥ 90: 3.5 (cm) (the same effect thickness increased by 40%)
[0258] Comparative Example 4 (mixing of conventional polyphenylene sulfide with gadolinium tungstate after polymerization)
[0259] Weigh 4600g of traditional polyphenylene sulfide The mixture was mixed with 400 g of synthesized gadolinium tungstate, and then granulated, spun and woven according to steps (4-7) of Example 1 to obtain a cloth with a thickness of 0.5 mm.
[0260] Test results:
[0261] i: Melt index (g / 10min, 315℃, 5kg): 270;
[0262] ii: Fiber melting point (℃): 281; Initial decomposition temperature (℃): 497
[0263] iii: Fiber strength (cN / dtex): 3.2 (20% lower than the example)
[0264] iv: gamma ray resistance (irradiation intensity does not drop by more than 10% of the dose): 10 8 Gy
[0265] v: X-ray (1meV) shielding efficiency (%) ≥ 90: 3.5 (cm) (35% increase in thickness for the same effect)
[0266] Comparative Example 5 (same as Comparative Example 4, with gadolinium tantalate replacing gadolinium tungstate)
[0267] Weigh 4600g of traditional polyphenylene sulfide 400 g of synthesized gadolinium tantalate was blended, and then granulated, spun and woven according to steps (4-7) of Example 1 to obtain a cloth with a thickness of 0.5 mm.
[0268] Test results:
[0269] i: Melt index (g / 10min, 315℃, 5kg): 270;
[0270] ii: Fiber melting point (℃): 281; Initial decomposition temperature (℃): 497
[0271] iii: Fiber strength (cN / dtex): 3.2 (20% lower than the example)
[0272] iv: gamma ray resistance (irradiation intensity does not drop by more than 10% of the dose Gy): 10 8
[0273] v: X-ray (1meV) shielding efficiency (%) ≥ 90: 3.5 (cm) (35% increase in thickness for the same effect)
[0274] Comparative Example 6 (This comparative example is to blend the composite material to which only the polycyclic active monomer is added with gadolinium tungstate)
[0275] 3.048 kg of the orange fine granules obtained by the preparation method of Comparative Example 2 were mixed with 0.302 kg of gadolinium tungstate, and then granulated, spun and woven according to steps (4-7) of Example 1 to obtain a cloth with a thickness of 0.5 mm.
[0276] Test results: The obtained composite material is not uniform and contains inorganic particles in the fibers.
[0277] i: Melt index (g / 10min, 315℃, 5kg): 137;
[0278] ii: Fiber melting point (℃): 282; Initial decomposition temperature (℃): 498
[0279] iii: Fiber strength (cN / dtex): 2.6 (decreased by about 50% compared with the example)
[0280] iv: gamma ray resistance (irradiation intensity does not drop by more than 10% of the dose Gy): 10 8
[0281] v: X-ray (1meV) shielding efficiency (%) ≥90: 2-5.0 (uneven) (cm) (same effect thickness increased by 35%) Comparative Example 7 (this comparative example uses the catalyst of CN110564154 B)
[0282] The catalyst "0.25 kg of γ-butyrolactone" in Example 1 was replaced with "0.25 kg of sodium nitrilotriacetate (NTA)", and the remaining steps were consistent with Example 1.
[0283] Test results:
[0284] i: Melt index (g / 10min, 315℃, 5kg): 215;
[0285] ii: Fiber melting point (℃): 282; Initial decomposition temperature (℃): 490
[0286] iii: Fiber strength (cN / dtex): 3.0 (30% lower than the example)
[0287] iv: gamma ray resistance (irradiation intensity does not drop by more than 10% of the dose Gy): 10 8
[0288] v: X-ray (1meV) shielding efficiency (%) ≥ 90: 3.0 (cm) (the thickness increases by 20% for the same effect).
Claims
1. A method for preparing a polyaromatic ring polyarylene sulfide-metal acid salt composite material, characterized in that: Under the protection of inert gas or N2, with polar aprotic solvent as medium, the composite salt, aromatic polycyclic active unit, dihalogenated aromatic compound and sulfide are copolymerized under the action of catalyst to obtain a composite material; Wherein, the composite salt is an insoluble metal acid salt, and the chemical formula is M a (N b O c ) d , where M is a rare earth element, N is W, Ta or Mo, O is an oxygen element, and a, b, c, d are all ≥ 1; The aromatic polycyclic active unit is a dihalogenated polycyclic aromatic hydrocarbon containing an active group, or a dihalogenated polycyclic aromatic hydrocarbon that can be hydrolyzed under alkaline conditions to produce an active group, and the active group is at least one of -OH and -COOH; The molar ratio of the aromatic polycyclic active unit to the dihalogenated aromatic compound is 1-10:999-90; The composite salt accounts for 0.5-20wt% of the total weight of the composite material.
2. The method for preparing the polyaromatic ring polyarylene sulfide-metal acid salt composite material according to claim 1, characterized in that: The M a (N b O c ) d In which, M is Gd, Lu, Eu or Er, and N is W or Ta; preferably, M is Gd; more preferably, a:d=2:3, c:b=3-4:1; further preferably, the composite salt is Gd2(WO4)3 or Gd2(Ta2O6)3; And / or, the aromatic polycyclic active unit is At least one of the following, wherein R1 and R2 are any one of halogens, and R1 and R2 are the same or different; preferably, the halogen is Cl or Br; more preferably, the aromatic polycyclic active unit is At least one of; And / or, the dihalogenated aromatic compound is a para-dihalogenated or meta-dihalogenated aromatic compound; preferably, the dihalogenated aromatic compound is selected from: 1,4-dihalobenzene, 2,4-dihalobenzene, 3,5-dihalobenzene, 4,4'-dihalobenzene, 4,4'-dihalobiphenyl, 4,4'-dihalodiphenyl sulfone, 4,4'-dihalobenzophenone or 4,4'-dihalodiphenyl ether; more preferably, the dihalogenated aromatic compound is 1,4-dichlorobenzene, 2,4-meta-dichlorobenzene, 4,4'-dichlorodiphenyl sulfone or 4,4'-dichlorobenzophenone.
3. The method for preparing the polyaromatic ring polyarylene sulfide-metal acid salt composite material according to claim 1, characterized in that: The catalyst is a lactone or a lactam; preferably, the catalyst is at least one of γ-butyrolactone, γ-valerolactone, ε-caprolactone, δ-cyclopentanolactone, γ-butyrolactam, δ-valerolactam, ε-caprolactam and ω-enantholactam; more preferably, the catalyst is used in an amount of 5-20wt% of the sulfide.
4. The method for preparing the polyaromatic ring polyarylene sulfide-metal acid salt composite material according to claim 1, characterized in that: The sulfide is at least one of sodium sulfide, sodium hydrosulfide, potassium sulfide, potassium hydrosulfide, ammonium sulfide, and ammonium hydrosulfide; preferably, the sulfide is sodium sulfide or sodium hydrosulfide; more preferably, the amount of the sulfide is calculated as follows: the amount of sulfide: the sum of the amount of the aromatic polycyclic active unit and the dihalogenated aromatic compound = 0.95-1.05:1.0; And / or, the polar aprotic solvent is selected from sulfone or sulfone compounds, amine compounds or lactam compounds; more preferably, the polar aprotic solvent is selected from: at least one of N-methyl-2-pyrrolidone, N-ethylpyrrolidone, N-cyclohexylpyrrolidone, 1,3-dimethyl-2-imidazole, hexamethylphosphoramide, N,N-dimethylacetamide, N,N-dimethylamide, caprolactam, N-ethylcaprolactam, N,N-vinylpyrrolidone, 1,3-dimethyl-2-imidazolidinone lactam, tetramethylurea, dimethyl sulfoxide or cyclopentane sulfone; further preferably, the amount of the polar aprotic solvent used is calculated according to the following ratio: the sum of the amounts of the aromatic polycyclic active units and the dihalogenated aromatic compounds: the volume of the polar aprotic solvent = 1:250-1500 mL.
5. The method for preparing the polyaromatic ring polyarylene sulfide-metal acid salt composite material according to claim 1, characterized in that: The copolymerization reaction conditions are: reaction temperature of 200-300°C, reaction time of 1-12h; preferably, first react at 200-250°C for 2-6h, then react at 250-300°C for 3-6h; more preferably, react at 220°C for 3h, then react at 260°C for 3h.
6. The method for preparing the polyaromatic ring polyarylene sulfide-metal acid salt composite material according to claim 1, characterized in that: After the copolymerization reaction, the polyaromatic ring polyarylene sulfide-metal acid salt composite material is washed and dried; preferably, the washing method is, after the copolymerization reaction is completed, first cooling to ≤180°C, then adding water to mix, filtering, washing and drying the polyaromatic ring polyarylene sulfide-metal acid salt composite material; more preferably, during washing, the temperature is reduced to below 150°C for washing.
7. A polyaromatic polyarylene sulfide-metal acid salt composite material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.
8. Polyaromatic ring polyarylene sulfide-metal acid salt composite flexible material, characterized in that: Granulating, spinning and weaving the polyaromatic ring polyarylene sulfide-metal salt composite material according to claim 7 to obtain a composite flexible material; Preferably, before spinning, the granulated copolymer composite material is dried; more preferably, the drying temperature is 120-150° C., and the drying time is 12-16 hours; more preferably, vacuum drum drying is used; Preferably, the spinning process is: the spinning temperature is 300-320° C., and the spinning speed is 600-1000 m / min.
9. The polyaromatic ring polyarylene sulfide-metal acid salt composite material according to claim 7 or the polyaromatic ring polyarylene sulfide-metal acid salt composite flexible material according to claim 8 is used for radiation shielding and protection.
